Cerebrospinal Fluid Bacillary Load by Xpert MTB/RIF Ultra Polymerase Chain Reaction Cycle Threshold Value Predicts 2-Week Mortality in Human Immunodeficiency Virus–Associated Tuberculous Meningitis - Martyn, Emily M; Bangdiwala, Ananta S; Kagimu, Enock; Rutakingirwa, Morris K; Kasibante, John; Okirwoth, Michael; Stead, Gavin; Wadda, Vincent; Pullen, Matthew F; Bold, Tyler D; Meya, David B; Boulware, David R; et al. (Clinical infectious diseases, 2021)
Abstract Background The World Health Organization recommends GeneXpert MTB/RIF Ultra (Xpert Ultra), a fully automated polymerase chain reaction (PCR) assay, as the initial tuberculous meningitis (TBM) diagnostic test. The assay’s PCR cycle threshold (Ct) values represent the number of PCR cycles required for probe signal to be detected (low Ct value = high bacillary load) and may approximate tuberculosis (TB) bacillary load. We measured the relationship between cerebrospinal fluid (CSF) TB bacillary load with mortality. Methods We prospectively enrolled 102 human immunodeficiency virus (HIV)–positive Ugandans with probable or definite TBM from April 2015 to August 2019. Xpert Ultra Ct tertiles and semi-quantitative categories were separately analyzed as predictors of 2-week mortality. We investigated associations between Ct and baseline clinical and CSF parameters. Results Subjects with Ct values in the low tertile (ie, high bacillary load) had 57% 2-week mortality—worse than the intermediate (17%) and high (25%) Ct tertiles and Xpert Ultra–negative (30%) probable TBM cases (P = .01). In contrast, the reported semi-quantitative Xpert Ultra categorization was less precise; with the medium to low category trending toward worse 2-week survival (42%) compared with very low (28%), trace (26%), and negative (30%) categories (P = .48). Ct tertile was significantly associated with baseline CSF lactate (P = .03). Conclusions High CSF TB bacillary load, as measured by Xpert Ultra Ct tertile, is associated with an almost 2-fold higher 2-week mortality in HIV-associated TBM and is a better predictor than the reported Xpert Ultra semi-quantitative category. Xpert Ultra Ct values could identify TBM patients at increased risk of death who may benefit from enhanced supportive care. High cerebrospinal fluid (CSF) tuberculosis bacillary load, as measured by GeneXpert Ultra cycle threshold tertile, is associated with an almost 2-fold higher 2-week mortality in HIV-associated tuberculosis meningitis and may be a better predictor of outcome than the reported Xpert Ultra semi-quantitative category.